(The Role of Transport and Tourism Economics in Achieving the Economic Development of the Kingdom of Saudi Arabia for the Period (2007-2017 - Al Mahanadi, Ban Ali Hussein (Journal of Economic, Administrative and Legal Sciences, 2019)
The transport sector in its various forms, has an important weight in tourist activity, it is a direct producer that deserves direct planning. It is coordinated with the objectives of the comprehensive tourism plan. Also, it is an important factor in the tourism industry where depend on it to transport tourists from outside their places of residence to the tourist destination. An analysis of the reality of transport and tourism activity in the Kingdom of Saudi Arabia shows the relative importance of the transport and communications sector, the relative importance of the retail sector, restaurants and hotels, the highest level of passenger services, In addition, there is the presence of religious tourism as the Kingdom of Saudi Arabia benefits from the influx of millions of Muslim pilgrims from all over the world to perform Hajj rituals annually and Umrah every day. And to see the archaeological sites and the holiest Bekaa in the Holy Haram area where in 2017 religious tourism attracted more than 8 million Muslim visitors, around 3 million came to perform Hajj. According to the National Transition Program, the Ministry of Hajj is committed to achieving the goal of providing the greatest possible number of Muslims to perform Hajj and Umrah. The end of this ministry is to increase the number of pilgrims from outside Saudi Arabia to 15 million by 2020 compared to 2017 (6.8 million) And according to Vision 2030, this number will double to 30 million by 2030, This is due to major growth in the fields of living accommodations, wellness maintenance, advanced shipping, retail and infrastructure. Equally part of its vision for growing the tourism sector and diversifying the sources of income, it intends to implement the first two projects, the Red Sea project and the second project of the city of Neum.
Keywords: transportation; tourism; future projects; economic development; religious